Collagenase‐Cleavable Peptide Amphiphile Micelles as a Novel Theranostic Strategy in Atherosclerosis. Issue 3 (3rd February 2020) - Chin, Deborah D.; Poon, Christopher; Trac, Noah; Wang, Jonathan; Cook, Jackson; Joo, Johan; Jiang, Zhangjingyi; Sta Maria, Naomi Sulit; Jacobs, Russell E.; Chung, Eun Ji
Abstract: Atherosclerosis is an inflammatory disease characterized by plaques that can cause sudden myocardial infarction upon rupture. Such rupture‐prone plaques have thin fibrous caps due to collagenase degradation, and a noninvasive diagnostic tool and targeted therapy that can identify and treat vulnerable plaques and may inhibit the onset of acute cardiac events. Toward this goal, monocyte‐binding, collagenase‐inhibiting, and gadolinium‐modified peptide amphiphile micelles (MCG PAMs) are developed. Monocyte chemoattractant protein‐1 (MCP‐1) binds to C‐C chemokine receptor‐2 expressed on pathological cell types present within plaques. Through the peptide binding motif of MCP‐1, MCG PAMs bind to monocytes and vascular smooth muscle cells in vitro. Moreover, using magnetic resonance imaging, MCG PAMs show enhanced targeting and successful detection of plaques in diseased mice in vivo and act as contrast agents for molecular imaging. Through the collagenase‐cleaving peptide sequence of collagen [VPMS‐MRGG], MCG PAMs can compete for collagenases that degrade the fibrous cap of plaques, providing therapy. MCG PAM‐treated mice show increased fibrous cap thickness by 61% and 113% histologically compared to nontargeting micelle‐ or PBS‐treated mice ( p  = 0.0075 and 0.001, respectively). Overall, this novel multimodal nanoparticle offers new theranostic opportunities for noninvasive diagnosis and treatment of atherosclerotic plaques. Abstract : Multimodal monocyte‐binding, collagenase‐inhibiting, and gadolinium‐modified peptide amphiphile micelles (MCG PAMs) are theranostic nanoparticles for atherosclerosis. Real‐time magnetic resonance imaging shows that MCG PAMs identify plaques in mice via monocyte and smooth muscle cell targeting. Histological analyses demonstrate that MCG PAM treatment enhances the fibrous cap thickness of plaques, thereby stabilizing atherosclerotic plaques from rupture in diseased mice.